Riding waves of intra-seasonal demand in surf tourism: analysing the nexus of seasonality and 21st century surf forecasting technology. Issue 2 (14th March 2020) - Mach, Leon; Ponting, Jess; Brown, James; Savage, Jessica
ABSTRACT: This study examines the natural component of seasonality in surf tourism. Using survey responses collected globally, we first analyse how surfers report using forecasts to make travel decisions. Occupancy and head-count data were also collected in Pavones, Costa Rica and analyzed against surf forecast data to empirically assess intra-seasonal fluctuations. Despite a small and highly skilled subset of the surf population, most international travel is booked months in advance based on climatic factors. Case study results indicate, however, that intra-seasonal travel behaviour within a country is correlated to both mid-range (occupancy) and short range (head-counts in the water) forecasts. Combined, surf forecasts and observed natural conditions impact surf travel behaviours in nuanced ways that deserve further attention to better understand destination and hospitality management, as well as, host and guest satisfaction and how they relate to intra-seasonal and intra-regional travel patterns.